Assessment of the Current State and Prospects for the Development of the Transport and Logistics System in Russia Federation in the Context of Risk Management - N. P. Stafeeva (North-West institute of management of the Russian Presidential Academy of National Economy and Public Administration, 2018)
In modern conditions of economic development, one of the drivers of the long-term growth of the real GDP of any country is its technological development, which, in the conditions of transition to an innovative trajectory of economic development, is manifested in innovation activity. Innovation in the form of scientific and technological progress is considered a key factor in the socio-economic development of the state. Prospects for the economic development of the Russian Federation, which are caused by the transition to an innovative model of development, actualize research in the field of the functioning of the innovation economy, including in relation to foreign economic policy, regulation of foreign economic activity and international innovation exchange. The study of risks in the international exchange of goods, services and knowledge for the management of supply chain risks, as well as the functioning of the risk management system, is an urgent state task. The article suggests classification of external risk factors. Based on the analysis of the functioning of the logistics industry in Russia, the main problems that lead to increased logistical costs are identified (undeveloped logistics infrastructure, inefficient supply chains, lack of clear logistics planning, ineffectiveness of the risk management system). It is concluded that in order to solve existing problems and improve the development of the logistics industry in Russia, it is necessary to solve the tasks of reducing security risks and ensuring the stability of supply chains.The successful solution of these tasks is conditioned by the formation and development of transport and logistics clusters and the implementation of innovative solutions in IT-support of logistics business processes.